Lean management and Islamic perspective: convergence in diversity - Abd. Manaf, Noor Hazilah; Zein, Ibrahim Mohamed (IIUM Press, 2011)
The lean philosophy is not an alien concept in Islam, although lean management is often attributed to the Toyota Production System (TPS). Central to the lean philosophy is the elimination of all form of waste or muda, in all work activities throughout the supply chain. Although the lean philosophy emerged out of the incapacity of Toyota to afford the waste inherent in mass production, nevertheless convergence in Islamic teachings is evident from the Qur’an and Sunnah. Muslims are constantly reminded against committing any acts of ‘israf’’ (waste). Thus, wasteful acts are seen as a disvalue in Islam from both the level of ethics of intent as well as the level of ethics of action. In addressing lean from an Islamic perspective, the stand is to establish relevancy along the line of mutual exchange and cultural meanings, with meaningful contribution of Muslim scholars towards human civilisation.